Soil microbial biomass phosphorus can serve as an index to reflect soil phosphorus fertility - Peng, Yi; Duan, Yisheng; Huo, Weige; Xu, Minggang; Yang, Xueyun; Wang, Xihe; Wang, Boren; Blackwell, Martin S. A.; Feng, Gu (Biology and fertility of soils, 2021)
The effect and relative contributions of C and P inputs on soil microbial biomass P (MBP) accumulation were studied in three long-term soil fertility experiments with various soil and climate characteristics at Qiyang, Yangling, and Wulumuqi. The maximum of soil MBP in all three sites was 47.8 mg P kg -1 . The MBP accumulated per unit in soil (mg P kg -1 soil) was correlated with a 4.91 mg kg -1 increase in Olsen P. For each unit increase in P surplus (kg P ha -1 ), manure C (kg C ha -1 ), and stubble C (kg C ha -1 ), MBP accumulation increased by 330, 3.7, and 13 units (μg P kg -1 soil), respectively. The soil MBP was positively correlated with crop yield and P uptake, making the soil MBP a useful soil P fertility index. The critical levels of the soil MBP pool were 140 kg ha -1 , 57–62 kg ha -1 , and 33–35 kg ha -1 in acidic red soil, loessial soil, and grey desert soil, respectively. This is the first report to establish a quantitative index of soil fertility based on the soil MBP pool. Our findings demonstrate that C input is a good driver of soil MBP accumulation. Integration of the soil MBP as an index of soil P fertility into agricultural P management is useful to help manage mineral P fertilizers as part of sustainable agricultural practices.